2007
DOI: 10.2903/j.efsa.2007.581
|View full text |Cite
|
Sign up to set email alerts
|

Neotame as a sweetener and flavour enhancer - Scientific Opinion of the Panel on Food Additives, Flavourings, Processing Aids and Materials in Contact with Food

Abstract: SUMMARYFollowing a request from the European Commission, the Scientific Panel on Food Additives, Flavourings, Processing Aids and Materials in Contact with Food (AFC) was asked to deliver a scientific opinion on the safety of neotame as a sweetener and flavour enhancer.Neotame is a dipeptide methyl ester derivate. Its chemical structure is N-[N-(3,3-dimethylbutyl)-L-α-aspartyl]-L-phenylalanine 1-methyl ester. It is intended for use in food as a sweetener and flavour enhancer. Neotame has a sweetness factor app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In the present study, we investigated the effect of neotame at concentrations ranging from 0.1 to 50 mM but noted intestinal epithelial cell death at 0.1 mM and intestinal barrier disruption at 1 µM. Furthermore, co-culture studies with E. coli or E. faecalis demonstrated pathogenic effects at 100 µM, which is lower than the expected concentration in many food and drink, and the acceptable daily intake (2,8). It is worth noting, however, that studies were performed following 24 h exposure to neotame whereas transit time in the intestine is 5 h therefore it is possible that the epithelium and gut microbiota would not be exposed to sustained sweetener for as long as was studied (51).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…In the present study, we investigated the effect of neotame at concentrations ranging from 0.1 to 50 mM but noted intestinal epithelial cell death at 0.1 mM and intestinal barrier disruption at 1 µM. Furthermore, co-culture studies with E. coli or E. faecalis demonstrated pathogenic effects at 100 µM, which is lower than the expected concentration in many food and drink, and the acceptable daily intake (2,8). It is worth noting, however, that studies were performed following 24 h exposure to neotame whereas transit time in the intestine is 5 h therefore it is possible that the epithelium and gut microbiota would not be exposed to sustained sweetener for as long as was studied (51).…”
Section: Discussionmentioning
confidence: 92%
“…Our previous studies have demonstrated that artificial sweeteners, sucralose, saccharin and aspartame, significantly reduce viability of intestinal epithelial cells ( 23 ) therefore our first experiments in this study assessed the impact of neotame on the intestinal epithelium in vitro at a range of physiological concentrations. Given that the ADI for neotame is approximately equivalent to 10 mM, we used up to this concentration for initial studies ( 8 ). There was a significant increase in Caco-2 cell viability at 1,000 μM neotame concentration exposure with higher concentrations showing very little cell viability (0.025 ± 0.005 a.u.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations